Chlamydia trachomatis Genital Tract Infections: When Host Immune Response and the Microbiome Collide. Issue 9 (September 2016) - Ziklo, Noa; Huston, Wilhelmina M.; Hocking, Jane S.; Timms, Peter
Abstract : Genital infections with Chlamydia trachomatis continue to be a major health problem worldwide. While some individuals clear their infection (presumed to be the result of an effective Th1/interferon-γ response), others develop chronic infections and some are prone to repeat infections. In females in particular, chronic asymptomatic infections are common and can lead to pelvic inflammatory disease and infertility. Recent studies suggest that the genital tract microbiota could be a significant factor and explain person-to-person variation in C. trachomatis infections. One hypothesis suggests that C. trachomatis can use its trpBA genes to rescue tryptophan from indole, which is a product of anaerobic members of the genital tract microbiota. Women with particular microbiota types, such as seen in bacterial vaginosis, have increased numbers of anaerobes, and this would enable the chlamydia in these individuals to overcome the host's interferon-γ attempts to eliminate it, resulting in more repeat and/or chronic infections. Trends: Some women are at higher risk of Chlamydia trachomatis infection and, particularly, repeat or chronic infections. Strains of C. trachomatis from the female genital tract are tryptophan auxotrophs but have retained the trpBA genes in the tryptophan biosynthetic pathway. This theoretically gives them the capacity to synthesise tryptophan from indole, if it is available. The female genital tract microbiota is a complex community that is dominated by lactobacilli, but the number of anaerobes increases during bacterial vaginosis. A recent hypothesis suggests that indole-producing anaerobes can be a source of exogenous indole, which Chlamydia can use to rescue tryptophan and overcome the host's interferon-γ assault to aid its replication.